Impact of Ultrasound-assisted Cooking and Endpoint Core Temperature on Physicochemical and Microbiological Properties, and Oxidative Stability of Beef - Dilara Aydın; Birol Kılıç; Azim Şimşek (Turkish Journal of Agriculture: Food Science and Technology)
This research aimed to investigate the impacts of different cooking methods (B; Boiling, US; Ultrasound-assisted slow boiling, UF; Ultrasound-assisted fast boiling) and endpoint core temperatures (ECT; 68°C, 74°C, and 80°C) on the oxidative stability, physicochemical, and microbiological properties of beef during refrigerated storage. The results demonstrated that UF application resulted in the lowest cooking loss (CL) at 74°C ECT. The US application caused a lower water activity (aw) compared to B. The lowest oxidation-reduction potential (ORP) levels were determined in UF, whereas the US had the highest ORP levels. Ultrasound-assisted cooking did not affect pH, yeast-mold and total mesophilic aerobic bacteria (TMAB) counts. On the other hand, UF and US caused an increase in total coliform counts compared to B. According to the results of lipid hydroperoxide (LPO) and thiobarbituric acid reactive substances (TBARS), UF application was more effective in preventing lipid oxidation compared to US and B. pH, CL, ORP, hue angle (hab) and b* values increased as the ECT increased, whereas aw, a*, chroma (C*ab) and browning index (BI; inner) values decreased. In addition, beef pieces cooked at 74°C or 80°C ECT had lower L* values, TMAB, and total coliform counts, and higher TBARS and LPO values than those cooked at 68°C ECT. 74°C was more effective in controlling microbiological changes, whereas 68°C was a better ECT for maintaining oxidative stability. In conclusion, UF has the potential to be an effective processing technology for improving oxidative stability and physicochemical properties of beef.